2001
DOI: 10.1055/s-2001-16941
|View full text |Cite
|
Sign up to set email alerts
|

C-Terminal Fragments of ACTH Stimulate Feeding in Fasted Rats

Abstract: Peptides derived from pro-opiomelanocortin, including alpha-MSH and ACTH, play important roles in the regulation of feeding. We investigated the central effect of ACTH 1-39 (ACTH) and peptides derived from the N-terminus (ACTH 1-10, Acetyl-ACTH 1-13-amide [alpha-MSH]) and C-terminus (ACTH 18-39 and ACTH 22-39) of this peptide on feeding in 16 hour-fasted or rats fed ad libitum. As expected, ACTH reduced feeding in fed and previously fasted rats, although this anorectic effect was more pronounced in fasted rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 19 publications
(21 reference statements)
2
15
0
1
Order By: Relevance
“…A potential role for ACTH in energy homeostasis is supported by observations that ACTH has a similar potency to ␣-MSH at the MC-4 receptor in vitro (Gantz et al, 1993), ACTH is secreted by the neurons of PVN (Pritchard et al, 2003), and ACTH can inhibit feeding when administered centrally to rats (Al-Barazanji et al, 2001). Single and repeated injections of ACTH antibodies into PVN resulted in persistently increased food intake during the light period.…”
Section: Behaviormentioning
confidence: 63%
“…A potential role for ACTH in energy homeostasis is supported by observations that ACTH has a similar potency to ␣-MSH at the MC-4 receptor in vitro (Gantz et al, 1993), ACTH is secreted by the neurons of PVN (Pritchard et al, 2003), and ACTH can inhibit feeding when administered centrally to rats (Al-Barazanji et al, 2001). Single and repeated injections of ACTH antibodies into PVN resulted in persistently increased food intake during the light period.…”
Section: Behaviormentioning
confidence: 63%
“…It was reported that the intracerebroventricular administration of -MSH inhibited food intake and increased energy expenditure in rodents [8,22,26,35]. In addition, when ACTH was injected into the lateral ventricle or into the ventromedial hypothalamus, food intake was reduced in both fed and fasted rats [1,36]. Its inhibitory effect on food intake was also confirmed in rabbits [2,26].…”
Section: Discussionmentioning
confidence: 59%
“…12 It is involved in energy balance and is an agonist to 4 out of 5 melanocortin receptors (MCR). 13 It is also anorexigenic in multiple species, including rats, 14 goldfish, 15 and chicks. 16 A lipolytic effect mediated through MC5R was reported in mouse 3T3-L1 cells, 17 but is yet to be determined in chicken or any other avian species.…”
Section: Introductionmentioning
confidence: 99%
“…2). 13,14 a-MSH promoted lipolysis in vitro 17 and in mice reduced their fat mass. 169,170 Signaling via MC5R increased lipolysis and impaired fatty acid re-esterification in 3T3-L1 adipocytes, 17 providing a plausible route of action of a-MSH in adipose tissue.…”
mentioning
confidence: 99%
See 1 more Smart Citation